2020
DOI: 10.18502/kss.v4i1.5997
|View full text |Cite
|
Sign up to set email alerts
|

Planning and Managing of Diagnostic Imaging Technologies in Healthcare: The Introduction of Managed Equipment Service (MES) for the System’s Sustainability

Abstract: The lack of resources has driven healthcare management studies to recognise Private and Public Partnerships (PPP) as the solution in managing efficiency, effectiveness and profitability of technological innovation. Recent researchers have identified the buying model called Managed Equipment Service (MES), in which purchaser and seller share the risks of technology’s management and use, as an optimal problem-solving method. The aim of this research is to analyse the potential economic-financial and organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The financial sustainability of publicly funded healthcare systems has been the main focus of researchers studying the economic aspect of sustainability [40]. It has been observed that achieving this objective poses a challenging task for policymakers in several countries.…”
Section: Introductionmentioning
confidence: 99%
“…The financial sustainability of publicly funded healthcare systems has been the main focus of researchers studying the economic aspect of sustainability [40]. It has been observed that achieving this objective poses a challenging task for policymakers in several countries.…”
Section: Introductionmentioning
confidence: 99%